The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1080/10862960903340165
|View full text |Cite
|
Sign up to set email alerts
|

English Language Learners: Developing Literacy in Second-Language Learners—Report of the National Literacy Panel on Language-Minority Children and Youth

Abstract: Based on concerns about the increasing numbers of English Language Learners in U.S. schools and the documented academic underperformance of this group, particularly in the domain of literacy, the federal government provided funding for a panel of experts to synthesize the knowledge base in the field and provide recommendations for future research. In 2006, the long awaited and much heralded

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
752
2
20

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 546 publications
(806 citation statements)
references
References 8 publications
32
752
2
20
Order By: Relevance
“…For example, Thai language plays great role in its education system, especially in rural areas and this substitution should be regarded at early stages (Maskhao, 2002). However, The National Literacy Panel found no indication that using native language make improvement or academic achievement (August & Shanahan, 2006). While some studies revealed significant differences in learning outcomes, using learners' native language or giving the opportunity to interact in their own language, can enhance learners' sense of competence and self-worth.…”
Section: The Principles Of Student-centered Learningmentioning
confidence: 99%
“…For example, Thai language plays great role in its education system, especially in rural areas and this substitution should be regarded at early stages (Maskhao, 2002). However, The National Literacy Panel found no indication that using native language make improvement or academic achievement (August & Shanahan, 2006). While some studies revealed significant differences in learning outcomes, using learners' native language or giving the opportunity to interact in their own language, can enhance learners' sense of competence and self-worth.…”
Section: The Principles Of Student-centered Learningmentioning
confidence: 99%
“…Research results are informative with respect to multilingual pupils: L1 maintenance proves beneficial to their educational success along with the study of the target language (August & Shanahan, 2006;Genesee et al ., 2006) . Time emerges as an important factor: Whereas interpersonal proficiency in a new language can be attained within two to four years, academic language takes five to seven (Thomas & Collier, 2002) and sometimes up to eleven years to develop (Levin & Shohamy, 2008) .…”
Section: Empirical Researchmentioning
confidence: 99%
“…Kindergarten pre-service teachers have difficulty discriminating English phonemes that do not already exist in their native language phonology (August et al, 2009;Escudero, 2014;Gilmore, 2011;Janzen, 2007;Yeung & Chan, 2012). For example, they do not always make the right predictions when reading is based on how they sound out a word, such as spelling "sed" instead of "said."…”
Section: Context Of the Problemmentioning
confidence: 99%
“…They must be able to identify, discriminate similar looking letters, and name each letter in the alphabet in order to make meaningful associations between letter symbols and their corresponding sound representations (Carson et al, 2015;Jamaludin et al, 2015;Pinto et al, 2015). Knowledge of the alphabetic principle refers to a realization that, in alphabetic orthographies, spoken words are comprised of phonemes and the phonemes are represented in text as letters (August et al, 2009;Gunning, 2009). …”
Section: Letter Knowledgementioning
confidence: 99%